Measurements of translational slug velocity and slug length using an image processing technique - Mohmmed, A.O. (Elsevier Ltd, 2016)
Slug flow is a common flow regime that occurs in various industries, such as oil, gas, and power generation industries. In this study, the mean slug translational velocity and slug liquid length were measured using Phantom 9.2 software and an image processing analysis technique. The adopted image processing technique involved the analysis of video frames recorded from a high-speed camera (Phantom 9.2) in a horizontal transparent pipe using a combination of the approximate median method and blob analysis, along with an additional morphological process for detecting and segregating individual slugs. The experimental data were obtained from a designed two-phase flow test section, in which sets of superficial water and air velocities were selected to generate numerous slug flows. A good agreement with a maximum deviation of 6.7 between the estimated slug parameters from the adopted technique and the Phantom cine view controller software was achieved. Additionally, the developed technique provided precise results with a high processing speed of 10 frames per second. Â© 2016 Elsevier Ltd.